When an event is not an event: The curious case of an emerging market - Utpal Bhattacharya; Hazem Daouk; Brian Jorgenson; Carl-Heinrich Kehr (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
Shares trading in the Bolsa mexicana de Valores do not seem to react to company news. Using a sample of Mexican corporate news announcements from the period July 1994 through June 1996, this paper finds that there is nothing unusual about returns, volatility of returns, volume of trade or bid-ask spreads in the event window. This suggests one of five possibilities: our sample size is small; or markets are inefficient; or markets are efficient but the corporate news announcements are not value-relevant; or markets are efficient and corporate news announcements are value-relevant, but they have been fully anticipated; or markets are efficient and corporate news announcements are value-relevant, but unrestricted insider trading has caused prices to fully incorporate the information. The evidence supports the last hypothesis. The paper thus points towards a methodology for ranking emerging stock markets in terms of their market integrity, an approach that can be used with the limited data available in such markets.
urn:nbn:de:hebis:30-9508
Keywords: G14; G15; 330; event study; insider trading; emerging markets